(untitled) (Texas Journal of Medical Science, 2026)
This article describes how to monitor the quality of care for women during pregnancy and childbirth for postpartum haemorrhage, evaluate the clinical and cost-effectiveness of care, standard requirements, and conduct surveys, patient reviews and prioritize complaints and appeals. . feedback on patient satisfaction monitoring